2014
DOI: 10.1186/s12974-014-0218-z
|View full text |Cite
|
Sign up to set email alerts
|

Signaling function of Na,K-ATPase induced by ouabain against LPS as an inflammation model in hippocampus

Abstract: BackgroundOuabain (OUA) is a newly recognized hormone that is synthesized in the adrenal cortex and hypothalamus. Low doses of OUA can activate a signaling pathway by interaction with Na,K-ATPase, which is protective against a number of insults. OUA has central and peripheral anti-inflammatory effects. Lipopolysaccharide (LPS), via toll-like receptor 4 activation, is a widely used model to induce systemic inflammation. This study used a low OUA dose to evaluate its effects on inflammation induced by LPS inject… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
64
0
8

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(78 citation statements)
references
References 67 publications
5
64
0
8
Order By: Relevance
“…There is a number of data indicating that ouabain can induce apoptotic cell death in various cell cultures as well as neurons . On the other hand, a lot of studies show that ouabain can increase the viability of kidney cells, endothelial cells and neurons . Reasons for opposing effects of ouabain remain poorly understood.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is a number of data indicating that ouabain can induce apoptotic cell death in various cell cultures as well as neurons . On the other hand, a lot of studies show that ouabain can increase the viability of kidney cells, endothelial cells and neurons . Reasons for opposing effects of ouabain remain poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…16,17 On the other hand, a lot of studies show that ouabain can increase the viability of kidney cells, [18][19][20] endothelial cells 21 and neurons. [22][23][24][25][26] Reasons for opposing effects of ouabain remain poorly understood. There is evidence that in neurons there are ouabain-triggered signalling cascades associated with mitogen-activated protein kinases (MAP kinases, or MAPK)-p38, JNK and ERK1/2, which are activated by phosphorylation and involved in regulation of cell death.…”
Section: Introductionmentioning
confidence: 99%
“…2H). It was not surprising to see that the GR pathway was activated after LPS injection, as several rodent models of endotoxemia have shown acute activation of the hypothalamic-pituitary-adrenal axis, leading to an increase in circulating corticosteroids (36)(37)(38)(39)(40). However, we found it intriguing that the GR pathway was ranked 8 on our LPS-regulated pathways in male mice, whereas it was ranked 5 in the females.…”
Section: Lps Challenge Leads To Sexually Dimorphic Hepatic Responses mentioning
confidence: 73%
“…Hence, ROS-induced activation of Na/K-ATPase signaling and downstream pathways generates further ROS through a feed-forward mechanism and creates an Na/K-ATPase oxidant amplification loop, which has been shown to be critical in a diseased state. While the cellular generation of ROS and the systemic redox imbalance evidently has been linked to the Na/K-ATPase/Src complex, the activation of this signaling mechanism can also be triggered by the release of CTS, like ouabain, which has been implicated in several diseased states [24][25][26][27][28]. Numerous studies have reported that Na/K-ATPase acts as a specific receptor for CTS.…”
Section: Mechanistic Insights Into Na/k-atpase Oxidant Amplification mentioning
confidence: 99%